Investigation of Extended Spectrum Beta-Lactamase Producing Escherichia coli and other Cefotaxime-Resistant Bacteria in Cow Milk in Nigeria (2021)
"Production of extended spectrum fl-lactamases (ESBLs) confers resistance to cefotaxime as well as many third and fourth generation cephalosporins in bacteria. ESBL-producing E. coli strains have been implicated in refractory infections in humans and dairy cows in Nigeria. The present study investigated thè presence of cefotaxime-resistant bacteria including ESBL-producing E. coli in thè milk of apparendy healthy cows from smallholder dairy herds. A total of 168 non-duplicate milk samples were collected from 34 catde herds in three locai government areas of Oyo State, Nigeria. Cefotaxime-resistant bacteria were isolated from milk samples by selective culture on MacConkey agar supplemented with cefotaxime (lmg/L). Isolates were identified by biochemical tests. Phenotypic ESBL production was determined using cefpodoxime/ cefpodoxime-clavulanic acid combinatìon discs. Presence of ESBL genes (Mttem, blasm and blacvx} and phylogenetic groups (A, Bl, B2, C, D, E, and F) of E. coli were determined by polymerase chain reaction assay. Susceptibility to other antimicrobials was carried out using thè Kirby-Bauer disk diffusion method. Cefotaxime-resistant bacteria were detected in milk samples of in 40 (23.8%) out of 168 individuai cows. At least one sample from 19 (55.9%) out of 34 herds yielded a cefotaxime-resistant isolate. The isolates were identified as Escherichia coli (9/168; 5.4%), Enterohacter amnigenus (8/168; 4.8%) and Pseudomonas aeruginosa (23/168; 13.7%). Five (3.0%) of all 168 samples were positive for phenotypic ESBL-producing bacteria. All thè ESBL-producing bacteria were E. coli and possessed blacrx-u which is of thè èlacvx-M-is gene variant. Two isolates also possessed thè blcrcem gene. ESBL-producing E. coli isolates belonged to phylogenetic groups A (n=3) and Bl (n=2). Overall, thè cefotaxime-resistant bacteria showed 100.0% resistance to ampicillin and cefotaxime, 90.0% to tetracycline, 72.2% to amoxicillin/clavulanic acid, 47.5% to streptomycin, 40.0% to sulphamethoxazole/trimethoprim, 37.5% to chloramphenicol, 32.5% to ceftazidime and 10.0% to each of ciprofloxacin and gentamicin. Keywords: ESBL Resistance Genes; Cow Milk; Cefotaxime-Resistance; Escherichia coli.